Pengaruh Motivasi Kerja dan Pengembangan Karir terhadap Kinerja Pegawai pada Kantor Badan Penanggulangan Bencana Daerah Kota Bima - Fita Sari; Mukhlis Mukhlis (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This study aims to examine the effect of: (1) To determine the Effect of Work Motivation on Employee Performance, (2) To determine the Effect of Career Development on Employee Performance, (3) To determine the Effect of Work Motivation and Career Development on Employee Performance at the Office of the Disaster Management Agency Bima city area. The type of research used in this research is associative. The population in the study were all employees at the Regional Disaster Management Agency Office, Kota Bima, totaling 62 people and a sample of 30 people using a purposive sampling technique. Data collection techniques used are observation, literature study and questionnaires. The data analysis technique used is validity test, reliability test, classic assumption test, multiple linear regression analysis, coefficient of determination, correlation coefficient, t test and f test. The results of the research based on the t test and f test show that: (1) Work Motivation has a positive and significant effect on employee performance (2) Career Development has a positive and insignificant effect on employee performance, (3) Work Motivation and Career Development have a simultaneous effect on employee performance at the Bima City Regional Disaster Management Agency office. x